2014
DOI: 10.1186/1471-2350-15-69
|View full text |Cite
|
Sign up to set email alerts
|

Five novel mutations in the ADAR1 gene associated with dyschromatosis symmetrica hereditaria

Abstract: BackgroundDyschromatosis symmetrica hereditaria (DSH) is an autosomal dominantly inherited skin disease associated with mutations of ADAR1, the gene that encodes a double-stranded RNA-specific adenosine deaminase. The purpose of this study was to investigate the potential mutations in ADAR1 in seven Chinese families with DSH.MethodsAll the coding exons including adjacent intronic as well as 5′ and 3′ untranslated region (UTR) of ADAR1 were screened by direct sequencing. Moreover, quantitative reverse-transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…A majority of these mutations were located in the deaminase domain, suggesting that a mutant ADAR1 could form a dysfunctional homodimer complex and impair wild-type ADAR1 activity. In addition to the known mutations, a recent study established that haploinsufficiency of ADAR1 p150 was a specific determinant of DSH [77]. The authors identified a novel ADAR1 p150 mutant that generates a premature termination codon, resulting in elimination of the mutant transcript.…”
Section: Good Editor Gone Bad: Diseases Associated With Mutations In mentioning
confidence: 95%
See 1 more Smart Citation
“…A majority of these mutations were located in the deaminase domain, suggesting that a mutant ADAR1 could form a dysfunctional homodimer complex and impair wild-type ADAR1 activity. In addition to the known mutations, a recent study established that haploinsufficiency of ADAR1 p150 was a specific determinant of DSH [77]. The authors identified a novel ADAR1 p150 mutant that generates a premature termination codon, resulting in elimination of the mutant transcript.…”
Section: Good Editor Gone Bad: Diseases Associated With Mutations In mentioning
confidence: 95%
“…The authors identified a novel ADAR1 p150 mutant that generates a premature termination codon, resulting in elimination of the mutant transcript. This mutation did not have any effect on the expression of ADAR p110, thereby providing new insights into the role of ADAR1 p150 in DSH pathogenesis [77]. Another disease associated with genetic mutations in ADAR1 is Aicardi-Goutières syndrome (AGS), an autoimmune disorder that primarily targets the brain and skin.…”
Section: Good Editor Gone Bad: Diseases Associated With Mutations In mentioning
confidence: 97%
“…In our study, no association was observed between these two polymorphisms (including A-20C and T174M) and EH among the both Hani and Yi populations. Previous researches have shown that the polymorphisms localized in the introns, 35,123 and exons, 124 close to the splice site would have effects on the process of mRNA splicing. In the bioinformatic analysis, it was observed that the c.620C>T (rs4762) led to the creation of new ESS (Motif 3, ESR, Motif 1, IIEs, Motif 2, Fas ) sites and the destruction of ESE (9G8, SC35, SF2/ASF(Ig), SF2/ ASF) sites, thereby weakening the splicing.…”
Section: Discussionmentioning
confidence: 99%
“…In general, only nine mutations on the ADAR1 coding sequence have been identified in AGS patients, compared to the more than 130 amino acids that have been found to be mutated in DSH patients. In addition to Hayashi et al′s list of known mutations [39], novel mutations in ADAR1 that are associated with DSH have also been identified [40,41,42,43,44,45], including an in-frame insertion that leads to mis-splicing [43]. …”
Section: Adar1′s Role In Immunitymentioning
confidence: 99%